2015
DOI: 10.1517/17425247.2016.1125879
|View full text |Cite
|
Sign up to set email alerts
|

Recentin vivoadvances in cell-penetrating peptide-assisted drug delivery

Abstract: Despite recent advances in the field, confusions surrounding CPP internalization mechanisms and intracellular trafficking are hindering the development of new and more efficient vectors. Nevertheless, the recent increase in the number of publications containing in vivo CPP utilization looks promising that the number of clinical trials would also increase in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
97
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 77 publications
0
97
0
2
Order By: Relevance
“…Further, as of 2015, more than 100 peptide therapeutics were in clinical trials for wide spectrum of clinical conditions, a number that is expected to increase in the future (7). It has also been shown that cell-penetrating peptides (CPPs) and other peptide delivery vehicles may be used to deliver macromolecules such as oligonucleotide (8) and promising small molecules to their intracellular targets (9). Results like these combined with a vast available sequence space will continue to drive peptide-based biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…Further, as of 2015, more than 100 peptide therapeutics were in clinical trials for wide spectrum of clinical conditions, a number that is expected to increase in the future (7). It has also been shown that cell-penetrating peptides (CPPs) and other peptide delivery vehicles may be used to deliver macromolecules such as oligonucleotide (8) and promising small molecules to their intracellular targets (9). Results like these combined with a vast available sequence space will continue to drive peptide-based biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, arginine-rich CPPs such as Tat peptide from a human immunodeficiency virus (HIV)-1 trans-activator protein TAT, [1][2][3] Penetratin peptide from a Drosophila homeodomain Antennapedia 4,5) and oligoarginines 6,7) show high efficiency of internalization, facilitating intracellular delivery of a wide range of hydrophilic molecules including small compounds, peptides, proteins, nucleic acids, nanoparticles, liposomes, and others that would be otherwise difficult to enter cells. [8][9][10] Arginine-rich CPPs have, therefore, attracted much attention as one of the promising carriers for intracellular delivery of therapeutic molecules including nucleic acids and drug candidates. [8][9][10] So far, a number of peptide sequences have been reported as CPPs, which are classified by their physicochemical characteristics, such as basic/amphiphilic CPPs that contain several basic amino acids including arginine and lysine, and hydrophobic CPPs (Table 1): interestingly, polyhistidine peptide such as histidine 16-mer (H16) is recently reported as CPPs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Arginine-rich CPPs have, therefore, attracted much attention as one of the promising carriers for intracellular delivery of therapeutic molecules including nucleic acids and drug candidates. [8][9][10] So far, a number of peptide sequences have been reported as CPPs, which are classified by their physicochemical characteristics, such as basic/amphiphilic CPPs that contain several basic amino acids including arginine and lysine, and hydrophobic CPPs (Table 1): interestingly, polyhistidine peptide such as histidine 16-mer (H16) is recently reported as CPPs. 11) Although the molecular mechanisms as to how argininerich CPPs enter cells have not been fully understood and still remain debated, it is commonly accepted that internalization of these peptides involves endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…To address this need, a new approach employing ''cell-penetrating peptides (CPPs)'' for drug delivery seems promising (Kurrikoff et al, 2016). They have the ability to enter cells via an unsaturated pathway, either alone or in conjugation with small molecules or bulky cargo.…”
Section: Introductionmentioning
confidence: 99%